Organic Agriculture and Foods for Sustainable Food Production and Safety, An updated Review - housny, Omer (Journal of King Abdulaziz University-Meteorology Environment and Arid Land Agriculture Sciences, 2023)
Recently, field crops with allelopathic activity have gained overwhelming importance in overcoming the adverse effects of chemical herbicides on the environment and the increasing weed resistance to herbicides. Among the many cover crops studied for their allelopathic activity, wheat has exhibited strong allelopathic activity against a wide range of weed species, as reported in the previous literature. Several previous studies have focused on identifying wheat allelochemicals responsible for the weed suppression effect. The current review represents details about the most critical and influential chemical groups, including benzoxazinoids and phenolic compounds. In addition, several methods have been reported to exploit the wheat's ability to combat weeds, including growing wheat in a crop rotation, applying wheat residues as soil mulch, or exposing weeds to wheat aqueous extract. A general background is also provided about allelopathy and allelochemicals; their concept, importance, chemical groups, mode of action and environmental impacts.